Study of Zn-Ni Alloy Coatings Modified by Nano-Al2O3 Particles Incorporation - Diafi, Malika; Temam, Elhachmi Guettaf; Gasmi, Brahim; Benramache, Said; Adaika, Mohamed Lakhdar (University of Eloued جامعة الوادي, 2018)
The aim of this research work was to codeposit nano-Al2O3 particles into Zn-Ni alloy coatings in order to improve some surface ,properties, the influence of the concentration of Al2O3 is the principal object in order to improve the corrosion resistance of the deposit, which has been made by electroplating on steel substrates previously treated, have been studied by several characterization methods, as the X-ray diffraction, measurement of micro hardness and scanning electron microscopy (SEM), protection against corrosion properties studied in a solution of 3% NaCl in the potentiodynamic polarization measurements (Tafel), electrochemical impedance spectroscopy (EIS) to the potential of corrosion free. The parameters that characterize the corrosion behavior can be determined from the plots and Nyquist plots and chronopotentiometry. Trends of increasing the charge transfer resistance and the decrease of capacitance values. XRD and SEM results and identify any coatings Zn- Ni and Zn-Ni-Al2O3 alloy composition have similar phase ( γ-phase structure) and the addition of Al2O3 in the Zn-Ni matrix increases the microhardness, and we note the maximum hardness is obtained for 50 g/L Al2O3.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Al2O3, Nickel, Zinc, EIS, XRD, SEM, chronopotentiometry